2020
DOI: 10.3390/brainsci10070445
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Isometric Wrist Flexion and Extension Maximal Voluntary Contractions on Corticospinal Excitability to Forearm Muscles during Low-Intensity Hand-Gripping

Abstract: The wrist extensors demonstrate an earlier fatigue onset than the wrist flexors. However, it is currently unclear whether fatigue induces unique changes in muscle activity or corticospinal excitability between these muscle groups. The purpose of this study was to examine how sustained isometric wrist extension/flexion maximal voluntary contractions (MVCs) influence muscle activity and corticospinal excitability of the forearm. Corticospinal excitability to three wrist flexors and three wrist extensors were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…Fatigue, defined as:” a symptom in which physical and cognitive function is limited by interactions between performance fatigability and perceived fatigability” [ 14 , 15 ], is a daily encountered condition that could be responsible for the kinematic changes observed in individuals with chronic RCRSP. It has been demonstrated that during upper limb work related tasks such as hammering [ 16 ], ratcheting [ 17 ] and simulated chain work [ 18 20 ], fatigue leads to kinematic adaptations, including decreased glenohumeral elevation, and increased trunk and scapular movements [ 14 , 15 , 21 ]. These observed kinematics changes following fatigue could be caused by different modulating factors [ 14 ] such as the reduction of proprioception acuity [ 15 ], muscle activation latency [ 22 ] and/or muscle force variability [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue, defined as:” a symptom in which physical and cognitive function is limited by interactions between performance fatigability and perceived fatigability” [ 14 , 15 ], is a daily encountered condition that could be responsible for the kinematic changes observed in individuals with chronic RCRSP. It has been demonstrated that during upper limb work related tasks such as hammering [ 16 ], ratcheting [ 17 ] and simulated chain work [ 18 20 ], fatigue leads to kinematic adaptations, including decreased glenohumeral elevation, and increased trunk and scapular movements [ 14 , 15 , 21 ]. These observed kinematics changes following fatigue could be caused by different modulating factors [ 14 ] such as the reduction of proprioception acuity [ 15 ], muscle activation latency [ 22 ] and/or muscle force variability [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that during upper limb work related tasks such as hammering [ 16 ], ratcheting [ 17 ] and simulated chain work [ 18 20 ], fatigue leads to kinematic adaptations, including decreased glenohumeral elevation, and increased trunk and scapular movements [ 14 , 15 , 21 ]. These observed kinematics changes following fatigue could be caused by different modulating factors [ 14 ] such as the reduction of proprioception acuity [ 15 ], muscle activation latency [ 22 ] and/or muscle force variability [ 23 , 24 ]. As kinematics changes could increase mechanical load on the shoulder joint and lead to injuries, it is important to better understand how fatigue influences shoulder movements, to assess its potential harmful effects and improve preventive interventions.…”
Section: Introductionmentioning
confidence: 99%